Lactylation as a cross-regulatory node in tumor metabolism and epigenetics: insights and therapeutic implications - Lv, Zhuangwei; Yang, Ruohao; Liu, Lulu; Shi, Xiaoyu; Wang, Ruihan; Wu, Jinhua; Jiao, Junna (Frontiers in Immunology, 2025)
Lactylation serves as a pivotal cross-regulatory mechanism linking tumor metabolic reprogramming and epigenetic regulation. This review comprehensively summarizes the mechanisms of lactylation writers, erasers, and readers, highlighting their tumor-specific functions, roles in immunosuppressive tumor microenvironment (TME) remodeling, and contributions to therapeutic resistance. Emerging targeting strategies, including metabolic inhibitors, epigenetic modulators, and combination immunotherapies, exhibit promising preclinical efficacy, highlighting their potential for clinical translation in overcoming therapy resistance and improving cancer immunotherapy.